2021
DOI: 10.3389/fnhum.2021.709275
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Theta Burst Stimulation to the Secondary Visual Cortex at 80% Active Motor Threshold Does Not Impair Central Vision in Humans During a Simple Detection Task

Abstract: Continuous theta burst stimulation (cTBS) is a powerful form of repetitive transcranial magnetic stimulation capable of suppressing cortical excitability for up to 50 min. A growing number of studies have applied cTBS to the visual cortex in human subjects to investigate the neural dynamics of visual processing, but few have specifically examined its effects on central vision, which has crucial implications for safety and inference on downstream cognitive effects. The present study assessed the safety of offli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
(77 reference statements)
0
1
0
Order By: Relevance
“…Additionally, studies using rs‐fMRI investigating the inhibitory and excitatory effects of cTBS and iTBS to motor, parietal and frontal brain regions have shown that these protocols modulate opposite connectivity patterns in focal and remote brain areas (Cocchi et al., 2015; de Wandel et al., 2020; Gratton et al., 2013). To date, however, only one rs‐fMRI study investigated the effects TBS to primary visual cortex (V1; Rahnev et al., 2013), and a few neuroimaging studies have examined the effects of TBS to specific nodes within the visual network (in areas beyond V1), for example, at the occipital cortex in visual category‐selective areas to measure changes at the stimulation site and FC between different vision‐related cortical and subcortical regions before and after TBS (Groen et al., 2021; Handwerker et al., 2020; Lasagna et al., 2021; Rahnev et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, studies using rs‐fMRI investigating the inhibitory and excitatory effects of cTBS and iTBS to motor, parietal and frontal brain regions have shown that these protocols modulate opposite connectivity patterns in focal and remote brain areas (Cocchi et al., 2015; de Wandel et al., 2020; Gratton et al., 2013). To date, however, only one rs‐fMRI study investigated the effects TBS to primary visual cortex (V1; Rahnev et al., 2013), and a few neuroimaging studies have examined the effects of TBS to specific nodes within the visual network (in areas beyond V1), for example, at the occipital cortex in visual category‐selective areas to measure changes at the stimulation site and FC between different vision‐related cortical and subcortical regions before and after TBS (Groen et al., 2021; Handwerker et al., 2020; Lasagna et al., 2021; Rahnev et al., 2013).…”
Section: Introductionmentioning
confidence: 99%